PERILAKU HIDUP SEHAT SISWA SEKOLAH MENENGAH ATAS NEGERI 2 BUNGARAYA DI MASA PANDEMI COVID-19 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is how the healthy lifestyle of senior high school state 2 of bungaraya students the Covid-19 pandemic which is currently being discussed. The purpose of this study was to determine the healthy behavior of senior high school state 2 of bungaraya students in the Covid-19 pandemic. The population in this study were 84 male students at SMA Negeri 2 Bungaraya. The sampling technique is total sampling. The instrument used in this study was a questionnaire. The data obtained were analyzed by using the% percentage test technique. Based on the research analysis, of the 84 respondents, around 43% or as many as 36 respondents were classified as very good, 56% or 47 respondents were classified as good, 1% or 1 respondent was classified as bad and 0% or 0 respondents were classified as very bad. Based on an average value of 124.5, the life behavior of students of SMA Negeri 2 Bungaraya in the Covid-19 pandemic was in the "Good" category.Key Words: Behavior, Healthy Life, Covid-19 Pandemic